Numerical investigation of long-span wing drone aeroelastic behavior using Lattice Boltzmann method - Kasicka, Adam (My University, 2025)
This work is focused on dealing with the fluid structure interaction (FSI), FSI is one of the great engineering challenges, due to its complexity that occurs when the fluid is acting on the object in the way that the object from the fluid flow forces is deforming and changing back the fluid flow behavior around the object. This type of interaction occurs in many different engineering challenges and is one of the key reasons why many people are drawn to the engineering field. The aim of this project is to conduct a fluid structure interaction analysis on the unmanned aerial vehicle Bayraktar TB2, and its impact on the performance from the deformation caused by the lift forces. Nowadays, there is a demand for drones as they can operate long distances with high accuracy and endurance, which means that for more demanding operations, these unmanned aerial vehicles are growing in size and speed [13]. As some of these drones have long-span wings, this means that they underlie a significant lift force in order to compensate for the weight, therefore, we will investigate how these long-span wings behave in cruise condition during the real mission. The geometry has been created with respect to the existing drone geometry, Bayraktar TB2. For the development of 3D geometry, we used OpenVSP, a software used to create aerospace geometries. The fluid model has been carried out and conducted with respect to the actual mission. The domain of numerical investigation of the fluid flow field has been carried out in Palabos, an open-source CFD software that uses the Lattice Boltzmann method. It is used for the advantages of reduced computational time and simple parallelization. CFD simulation is used to define the forces acting on the geometry and also to evaluate the performance of the drone. In order to model the deformation of the long-span wings, we will use the forces from the CFD simulation as boundary conditions, the main focus will be on the lift, as this force will be significantly higher than drag. For structural simulation, we will use the Ansys static structural solver to investigate and model the wing deformation. After the structural simulation, we will export the deformed geometry to use it in the CFD simulation to investigate changes in performance and the flow field. The differences in performance have been analyzed, and the results have been compared to judge whether or not the deformation significantly reduces the performance of the long-span wing drone in the cruise conditions.
Keywords: FSI; drone; Lattice Boltzmann method; CFD; FEM; aerodynamics; wing deformation; lift force; drag force.